Current Imaging Strategies in Patients with Abdominal Aortic Aneurysms - Ristow, Inka; Riedel, Christoph; Lenz, Alexander; Well, Lennart; Adam, Gerhard; Panuccio, Giuseppe; Kölbel, Tilo; Bannas, Peter (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Background An abdominal aortic aneurysm (AAA) is defined as a localized dilatation of the abdominal aorta of ≥ 3 cm. With a prevalence of 4–8 %, AAA is one of the most common vascular diseases in Western society. Radiological imaging is an elementary component in the diagnosis, monitoring, and treatment planning of AAA patients.Method This is a narrative review article on preoperative imaging strategies of AAA, incorporating expert opinions based on the current literature and standard-of-care practices from our own center. Examples are provided to illustrate clinical cases from our institution.Results and Conclusion Radiological imaging plays a pivotal role in the initial diagnosis and monitoring of patients with AAA. Ultrasound is the mainstay imaging modality for AAA screening and surveillance. Contrast-enhanced CT angiography is currently considered the gold standard for preoperative imaging and image-based treatment planning in AAA repair. New non-contrast MR angiography techniques are robustly applicable and allow precise determination of aortic diameters, which is of critical importance, particularly with regard to current diameter-based surgical treatment guidelines. 3D imaging with multiplanar reformation and automatic centerline positioning enables more accurate assessment of the maximum aortic diameter. Modern imaging techniques such as 4D flow MRI have the potential to further improve individualized risk stratification in patients with AAA.Key points:
Keywords: abdominal aortic aneurysm; intraluminal thrombus; angiography; growth prediction; diameter